Fighting for lemons: The encouragement effect in dynamic contests with private information - Juan Beccuti; Marc Möller (University of Bern, Department of Economics, 2020)
This paper proposes a tractable model of a dynamic contest where players have private information about the contest's prize. We show that private information helps to encourage players who have fallen behind, leading to an increase in aggregate incentives. We derive the optimal information design for a designer interested in the maximization of aggregate effort. Optimal signals turn out to be private and imperfectly informative and aim to level the playing field at any stage of the dynamic interaction.
Keywords: C72; D72; D82; 330; Dynamic contests; discouragement effect; information design